2019
DOI: 10.3389/fgene.2019.00652
|View full text |Cite
|
Sign up to set email alerts
|

Omics Driven Understanding of the Intestines of Parasitic Nematodes

Abstract: The biological and molecular complexity of nematodes has impeded research on development of new therapies for treatment and control. We have focused on the versatility of the nematode intestine as a target for new therapies. To that end, it is desirable to establish a broad and deep understanding of the molecular architecture underlying intestinal cell functions at the pan-Nematoda level. Multiomics data were generated to uncover the evolutionary principles underlying both conserved and adaptable features of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…As one example, our research has focused on the nematode intestine due to its apparent hypersensitivity to some anthelmintics and because it has relative tractability to experimental approaches compared to other tissues ( Jasmer et al, 2019 ). In recent progress ( Jasmer et al, 2020 ), we identified a set of nematode intestinal toxins/toxicants (NITs) that caused apparent irreparable intestinal cell damage in A. suum L3 and L4.…”
Section: Introductionmentioning
confidence: 99%
“…As one example, our research has focused on the nematode intestine due to its apparent hypersensitivity to some anthelmintics and because it has relative tractability to experimental approaches compared to other tissues ( Jasmer et al, 2019 ). In recent progress ( Jasmer et al, 2020 ), we identified a set of nematode intestinal toxins/toxicants (NITs) that caused apparent irreparable intestinal cell damage in A. suum L3 and L4.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal helminth infections are common in man and animals, especially in developing regions of Africa, Asia and the Americas [1][2][3]. These parasitic infections generate substantial mortality and morbidity and produce relevant physical and mental disorders and often persist in the face of serious economic problems [2].…”
Section: Author's Summary Introductionmentioning
confidence: 99%
“…These parasitic infections generate substantial mortality and morbidity and produce relevant physical and mental disorders and often persist in the face of serious economic problems [2]. Moreover, infections by intestinal helminths also compromise the health and productivity of livestock worldwide [3]. Currently, the impact of intestinal helminth infections only can be reduced by anthelminthic treatment, but the progressive emergence of resistances to these drugs limits their utility.…”
Section: Author's Summary Introductionmentioning
confidence: 99%
“…Intestinal helminth infections are common in man and animals, especially in developing regions of Africa, Asia and the Americas [1][2][3]. These parasitic infections generate substantial morbidity and produce relevant physical and mental disorders and often persist in the face of serious economic problems [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, infections by intestinal helminths also compromise the health and productivity of livestock worldwide [3]. Currently, the impact of intestinal helminth infections mainly can be reduced by anthelminthic treatment, but the progressive emergence of resistances to these drugs limits their utility.…”
Section: Introductionmentioning
confidence: 99%